36.1k views
1 vote
(tan theta+ cot theta)^2= sec^2 theta+cosec^2 theta​

1 Answer

3 votes

Answer:

Proved that
(\tan \theta + \cot \theta)^(2) = \sec^(2) \theta + \csc^(2) \theta.

Explanation:

We have to prove that


(\tan \theta + \cot \theta)^(2) = \sec^(2) \theta + \csc^(2) \theta

Now, Left hand side

=
(\tan \theta + \cot \theta)^(2)

=
\tan^(2) \theta + 2* \tan \theta * \cot \theta + \cot^(2) \theta {Since we know the formula (a + b)² = a² + 2ab + b²}

=
\tan^(2) \theta + 2 + \cot^(2) \theta

{Since
\tan \theta * \cot \theta = 1}

=
(\tan^(2) \theta + 1) + (\cot^(2) \theta + 1)

=
\sec^(2) \theta + \csc^(2) \theta

{Since we know the identities:


\sec^(2) x = \tan^(2) x + 1 and
\csc^(2) x = \cot^(2) x + 1}

= Right hand side

Hence, proved.

User VBK
by
5.2k points